Creating Video-Based Education Modules for Parents of Newly Diagnosed Pediatric Patients With Cancer. Issue 2 (March 2022) - Mills, Denise; Zupanec, Sue; Breakey, Vicky; Chakkalackal, Lauren; Cook, Sadie; Cox, Stephanie; Gibson, Paul; Punnett, Angela; Sung, Lillian
Abstract : Background: Parents of children newly diagnosed with cancer are required to understand a significant amount of new information during a time of distress. Parents of children with cancer have expressed that concise information with visual cues, which can be repeated, positively influences their ability to understand. Objectives: The primary objective was to develop 2 concise, video-based education modules that are understandable to parents of children with cancer. A secondary objective was to determine feasibility of a future trial evaluating efficacy of video-based education. Methods: The study was conducted in phases: script development, video creation, and feasibility testing. Topics were "managing fever at home" and "giving medications at home." Content was developed by pediatric oncology experts and turned into video scripts. Scripts were refined through cognitive interviews with parents of children with cancer. Feasibility testing included recruitment of 20 parents of a child given a diagnosis of cancer within 4 weeks. Parents watched both videos and answered questions that assessed their understanding and perceived confidence. Results: Final scripts were reviewed by 25 participants. Feasibility was achieved with 20 parents recruited within 7 weeks, with 100% watching both videos and answering knowledge and confidence questions. Conclusions: We successfully developed 2 educational videos for parents of children newly diagnosed with cancer. A future trial to test the efficacy of video-based education modules is feasible. Implications to Practice: Delivering quality education to parents of children newly diagnosed with cancer can decrease parental distress and improve safe care during a high-risk time for treatment-related morbidity and mortality.